Analysis of Primary School Teachers’ Opinions on Family Diversity - Capano Bosch, Alvaro (2016)
This article aims to do an analysis based on the opinion of primary school teachers on family models that are different from the traditional nuclear family.  We worked with 60 teachers from Montevideo and the metropolitan area.  They answered the Questionnaire: Teachers' Opinion on Family Diversity (CIDF for its Spanish acronym) (Morgado, Jimenez-Lagares & Gonzalez, 2009).  The data indicate that teachers do not share a homogeneous point of view regarding the different household types. Adoptive families, divorced parents families, and single-parent families headed by single mothers had a better acceptance among teachers than homoparental families or those headed by single fathers.  Items related to homoparental families were answered by fewer people. Teachers with postgraduate education were more tolerant and flexible towards family diversity. These results are discussed in light of the necessary adaptations in primary education with respect to the diversity of families existing there.